Core-shell ammoxidation catalyst, preparation method and application thereof, and acrylonitrile synthesis method
By regulating the catalyst particle structure, a core-shell ammonia oxidation catalyst was prepared, which solved the problem of volatility of molybdenum components in the prior art, and achieved long-term stable operation of the catalyst under high load and efficient acrylonitrile synthesis.
Patent Information
- Application Number
- CN202310781611.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-28
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2043-06-28
AI Technical Summary
The existing ammonia oxidation catalysts are prone to volatilization under high temperature and high load conditions, resulting in poor catalyst stability and need to be continuously supplemented to maintain stable reaction operation.
By regulating the catalyst particle structure, pre-hydrolyzing the precursor of molybdenum and introducing molybdenum trioxide, a new catalyst with a core-shell structure was prepared. The main components of the core include bismuth molybdate, molybdenum trioxide and carrier, and the main components of the outer shell include molybdenum acid Salt and carrier to reduce volatile loss of molybdenum components.
The long-term and stable operation of the catalyst under high load is achieved, the propylene conversion rate and acrylonitrile single-pass yield are maintained, the volatility loss of molybdenum components is reduced, and the activity and stability of the catalyst is improved.
Smart Images

Figure CN119236960A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalyst preparation, and in particular to a core-shell ammoxidation catalyst, a preparation method and application thereof, and a method for synthesizing acrylonitrile. Background Art
[0002] Acrylonitrile, as an important organic chemical raw material, is widely used in many fields such as synthetic fibers and synthetic resins. Recently, with the rapid development of ABS (acrylonitrile-butadiene-styrene copolymer) resin and acrylonitrile-based carbon fiber, the downstream demand for acrylonitrile is growing. At present, the production process of acrylonitrile is mainly Sohio method, that is, using propylene as raw material, acrylonitrile is synthesized in a fluidized bed reactor through an ammoxidation process, and the catalyst used is mainly Mo-Bi system composite oxide.
[0003] In actual applications, it is found that after long-term operation in a fluidized bed reactor, especially under high temperature and high load conditions, the molybdenum component is easily volatile and often loses seriously, which not only causes the loss of catalyst but also seriously affects the long-term stability of catalytic activity. At present, the process equipment often needs to continuously replenish the catalyst to maintain the stable operation of the reaction. Therefore, a key research direction of catalysts in this field is to develop a new catalyst for propylene ammoxidation to acrylonitrile that can reduce the loss of active molybdenum components under high temperature and high load and can operate stably for a long time.
[0004] In order to solve the problem of long-term operation stability of acrylonitrile catalysts, researchers have conducted a lot of research on catalyst carrier components. CN100566829 uses silicon dioxide, aluminum oxide or a mixture thereof as a carrier, and the catalyst can run smoothly at a lower ammonia ratio, air ratio and lower temperature, which improves the reaction yield and stability of the acrylonitrile catalyst and reduces the content of by-products such as carbon and hydrocyanic acid; CN101284237 modifies the carrier with small molecule template agents such as tetraethylamine and tetrapropylamine, and composites it with active components to obtain an acrylonitrile catalyst with good activity, selectivity, anti-reduction and anti-wear resistance; CN102892498 obtains a catalyst with a specific X-ray diffraction pattern by adjusting and controlling the components of the auxiliary agent, which can be widely used in the preparation of acrylonitrile, methacrylonitrile, etc. by olefin ammoxidation, which improves the conversion rate of the reaction. CN110562990 proposes to use silica sol with a particle size uniformly distributed in the range of 20 to 30 nanometers, a viscosity less than 20 cPs, a mass concentration of not less than 40%, and an added stabilizer as a carrier to prepare acrylonitrile. The silica sol has a stability time of more than 20 minutes and has good stability, which is suitable for large-scale industrial production. CN113828322 focuses on the volatile molybdenum trioxide component in the acrylonitrile catalyst, and prepares molybdenum trioxide with a specific X-ray spectrum. The molybdenum trioxide and the molybdenum-based acrylonitrile catalyst body form a feeding system, which is used in the continuous feeding process of the propylene ammoxidation reaction, and can obtain a higher acrylonitrile yield at a higher propylene load, and maintain stability for a long time. Summary of the invention
[0005] The purpose of the present invention is to overcome the problem of poor stability of ammonia oxidation catalysts in the prior art and to provide a new core-shell ammonia oxidation catalyst and a preparation method thereof, in particular, the application of the catalyst in the synthesis of acrylonitrile.
[0006] As mentioned above, the current methods for improving the stability and activity of acrylonitrile catalysts mainly focus on changes in their components, such as increasing the types of metal elements, adjusting the carrier composition, etc., while there are relatively few studies on the regulation of the catalyst particle structure. Based on this, the inventors of the present invention proposed through research that, without changing the basic element components of the acrylonitrile catalyst, by regulating the structure of the catalyst particles, the molybdenum content inside the catalyst particles is increased by pre-hydrolyzing the molybdenum precursor and additionally introducing molybdenum trioxide, a new acrylonitrile catalyst with a core-shell structure is prepared. The main components of the catalyst kernel include bismuth molybdate, molybdenum trioxide and a carrier; the main components of the catalyst shell include molybdate and a carrier.
[0007] Based on the research of the inventors of the present invention, the first aspect of the present invention provides a core-shell ammonia oxidation catalyst, the catalyst comprising a carrier and an active component; the general formula of the active component is Mo 10 Bia B b C c D d O x ; B is selected from at least one of the Group VIII metal elements; C is selected from at least one of the alkaline earth metal elements; D is selected from at least one of the alkali metal elements; a, b, c and d respectively represent the molar content of Bi, B, C and D relative to Mo; a is in the range of 0.05-8.0, b is in the range of 0.02-10.0, c is in the range of 0.02-6.0, d is in the range of 0.05-5.0, and x is determined by the atomic ratio and valence state of the elements other than oxygen in the general formula of the active component; wherein Mo exists simultaneously in the form of bismuth molybdate, molybdenum trioxide and molybdate; the mesostructure of the catalyst includes an inner core and an outer shell; the main components of the inner core of the catalyst include bismuth molybdate, molybdenum trioxide and a carrier; the main components of the outer shell of the catalyst include molybdate and a carrier.
[0008] The second aspect of the present invention provides a method for preparing the above catalyst, the preparation method comprising:
[0009] (1) a molybdenum precursor, a bismuth precursor, a molybdenum trioxide powder, and a carrier source are mixed and contacted in a solution, and then hydrolyzed and compounded under acidic conditions to obtain a precursor of a core structure;
[0010] (2) The precursor of the core structure, the precursor of B, the precursor of C, the precursor of D and the surfactant are mixed and contacted in a solution, and then dried and calcined to obtain the catalyst.
[0011] The third aspect of the present invention provides the use of the catalyst of the present invention in the preparation of nitrile compounds from C2-C5 hydrocarbon compounds.
[0012] A fourth aspect of the present invention provides a method for synthesizing acrylonitrile, the method comprising: subjecting propylene to an ammoxidation reaction under mixed gas conditions of an oxygen-containing atmosphere and ammonia.
[0013] Compared with the prior art, the present invention has at least the following beneficial effects:
[0014] (1) The catalyst of the present invention has a core-shell structure, wherein the inner core is molybdate / molybdenum oxide / carrier component, and the outer shell is molybdate / carrier component. This structure helps to reduce the volatilization loss of the molybdenum component during long-term operation, thereby achieving long-term stable operation of the catalyst under high load;
[0015] (2) The catalyst of the present invention is used in the synthesis method of acrylonitrile, and after long-term operation, it can still maintain a relatively high propylene conversion rate and acrylonitrile per-pass yield. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1Graph showing the change in Mo element intensity in the ammonia oxidation catalyst particles of Example 1 in the radial direction (from the center of the catalyst particles to the surface of the catalyst particles). DETAILED DESCRIPTION
[0017] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0018] The first aspect of the present invention provides a core-shell ammonia oxidation catalyst, the catalyst comprising a carrier and an active component; the general formula of the active component is Mo 10 Bi a B b C c D d O x ; B is selected from at least one of the Group VIII metal elements; C is selected from at least one of the alkaline earth metal elements; D is selected from at least one of the alkali metal elements; a, b, c and d represent the molar content of Bi, B, C and D relative to Mo respectively; a is in the range of 0.05-8.0, b is in the range of 0.02-10.0, c is in the range of 0.2-6.0, d is in the range of 0.05-5.0, and x is determined by the atomic ratio and valence state of the elements other than oxygen in the general formula of the active component; wherein Mo exists simultaneously in the form of bismuth molybdate, molybdenum trioxide and molybdate;
[0019] The mesoscopic structure of the catalyst comprises an inner core and an outer shell; the main components of the inner core of the catalyst comprise bismuth molybdate, molybdenum trioxide and a carrier; the main components of the outer shell of the catalyst comprise molybdate and a carrier.
[0020] In the present invention, the components in the core and the shell can be obtained by scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS) testing, wherein the core and the shell form a core-shell structure.
[0021] In the present invention, "Mo 10 Bi a B b C c D d O x The general formula of " merely represents the individual elements and their molar contents of the active components in the catalyst, and does not mean that the active components of the catalyst in the present invention exist as molecules of the general formula.
[0022] In the present invention, the inner core of the catalyst is in close contact with the outer shell.
[0023] In the present invention, the molybdate in the shell component of the present invention refers to molybdates of elements B, C and D, such as magnesium molybdate, iron molybdate and the like.
[0024] In the present invention, by studying the regulation of the particle structure of the catalyst and regulating the structure of the catalyst particles, the catalyst core contains molybdenum trioxide. The catalyst core contains bismuth molybdate, molybdenum trioxide and a carrier, and the outer shell contains molybdate and a carrier. This structure helps to reduce the volatilization loss of the molybdenum component during long-term operation, thereby achieving long-term stable operation of the catalyst under high load.
[0025] According to the present invention, as long as the purpose of the present invention can be achieved, the content of each element in the active component is not particularly limited. In some preferred embodiments, a is in the range of 0.05-4 (e.g., 0.05, 0.1, 0.3, 0.4, 0.5, 1, 2, 3 or 4); in some preferred embodiments, b is in the range of 0.1-10 (e.g., 0.1, 0.5, 1, 2, 4, 5, 7, 8, 9 or 10); in some preferred embodiments, c is in the range of 0.1-6 (e.g., 0.1, 0.5, 1, 2, 4, 5 or 6), and d is in the range of 0.05-2 (e.g., 0.05, 0.06, 0.07, 0.1, 0.2, 0.5, 1, 1.5 or 2). The above-mentioned embodiments can better increase the catalytic activity of the catalyst when used for ammoxidation reaction.
[0026] According to the present invention, in some embodiments, the molybdenum content of the core and the shell is different based on the total weight of the molybdenum in the catalyst. By adopting the above embodiment, the effect of long-term stable operation of the catalyst under high load is achieved.
[0027] According to the present invention, in some embodiments, the content of molybdenum in the core is higher than the content of molybdenum in the shell, based on the total weight of molybdenum in the catalyst. The above-mentioned embodiment helps to reduce the volatilization loss of molybdenum components during long-term operation, thereby achieving long-term stable operation of the catalyst under high load.
[0028] According to the present invention, in some preferred embodiments, based on the total amount of molybdenum in the catalyst, the content of molybdenum in the core is 60-80wt%, and the content of molybdenum in the shell is 20-40wt%. The above embodiments can better increase the activity and stability of the catalyst.
[0029] According to the present invention, in some preferred embodiments, based on the total amount of the carrier in the catalyst, the carrier in the core accounts for 50-65wt% of the total amount of the carrier in the catalyst, and the carrier in the shell accounts for 35-50wt% of the total amount of the carrier in the catalyst. The above embodiment can better increase the activity and stability of the catalyst.
[0030] According to the present invention, in some preferred embodiments, based on the total amount of bismuth in the catalyst, the bismuth in the inner core accounts for 55-65wt% of the total amount of bismuth in the catalyst, and the bismuth in the outer shell accounts for 35-45wt% of the total amount of bismuth in the catalyst. The above embodiment can further increase the catalytic activity and stability of the catalyst in the ammoxidation reaction.
[0031] According to the present invention, in some preferred embodiments, based on the total amount of B element in the catalyst, the B element in the core accounts for 30-45wt% of the total amount of B element in the catalyst, and the B element in the shell accounts for 55-70wt% of the total amount of B element in the catalyst. The above embodiment can further increase the activity and stability of the catalyst.
[0032] According to the present invention, in some preferred embodiments, based on the total amount of C element in the catalyst, the C element in the core accounts for 30-45wt% of the total amount of C element in the catalyst, and the C element in the shell accounts for 55-70wt% of the total amount of C element in the catalyst. The above embodiment can further increase the activity and stability of the catalyst.
[0033] According to the present invention, in some preferred embodiments, based on the total amount of D element in the catalyst, the D element in the core accounts for 35-45wt% of the total amount of D element in the catalyst, and the D element in the shell accounts for 55-65wt% of the total amount of D element in the catalyst. The above embodiment can further increase the activity and stability of the catalyst.
[0034] According to the present invention, in some embodiments, B is selected from at least one of iron, cobalt, nickel, ruthenium, rhodium, palladium, osmium, iridium and platinum, preferably at least one of iron, cobalt and nickel. The above embodiments can increase the activity and stability of the catalyst.
[0035] According to the present invention, in some embodiments, C is selected from at least one of magnesium, calcium, strontium and barium, preferably magnesium and / or calcium. The above embodiments can increase the activity and stability of the catalyst.
[0036] According to the present invention, in some embodiments, D is selected from at least one of sodium, potassium, rubidium and cesium, preferably potassium. The above embodiments can further increase the activity of the catalyst and the long-term stable operation under high load.
[0037] According to the present invention, in some preferred embodiments, the specific surface area of the catalyst is 35-60m 2 The catalyst under the aforementioned embodiment is more conducive to the contact between the catalyst and the reaction substrate.
[0038] According to the present invention, in some preferred embodiments, the pores with a pore size of 20-35 nm on the inner core account for 40-50% of the total pores of the catalyst. The above embodiments can better increase the catalytic activity of the catalyst and the selectivity of the nitrile target product.
[0039] According to the present invention, in some preferred embodiments, the pores with a pore size of 6-12 nm on the shell account for 50-60% of the total pores of the catalyst. The above-mentioned embodiment can better increase the stability of the catalyst. The inventors speculate that the shell structure has a good protective effect on the core, limiting the loss of the core active components through the shell pores.
[0040] According to the present invention, in some preferred embodiments, the radius of the catalyst particle is from the center of the catalyst particle to the particle surface, the radius of the inner core is 40-60% of the radius of the catalyst particle, and the portion along the surface of the inner core toward the catalyst particle surface is the outer shell.
[0041] According to the present invention, it can be understood that the center of the inner core is consistent with the center of the catalyst particle, and the radius of the catalyst particle is from the center of the catalyst particle to the surface of the particle. 40-60% (for example, 40%, 42%, 45%, 50%, 52%, 55%, 58% or 60%) of the radius is divided into the inner core of the catalyst and the outer shell of the catalyst.
[0042] According to the present invention, as long as the purpose of the present invention can be achieved, the content of the active component and the carrier is not particularly limited. In some embodiments, the mass ratio of the active component to the carrier is (1.5-0.8): 1, preferably (1.2-1.0): 1. The above-mentioned embodiment can better increase the activity of the catalyst and the long-term stable operation under high load.
[0043] According to the present invention, as long as the purpose of the present invention can be achieved, the type of the carrier is not particularly limited. In some embodiments, the carrier includes aluminum oxide and / or silicon oxide.
[0044] The second aspect of the present invention provides a method for preparing the above catalyst, the preparation method comprising:
[0045] (1) a molybdenum precursor, a bismuth precursor, a molybdenum trioxide powder, and a carrier source are mixed and contacted in a solution, and then hydrolyzed and compounded under acidic conditions to obtain a precursor of a core structure;
[0046] (2) The precursor of the core structure, the precursor of B, the precursor of C, the precursor of D and the surfactant are mixed and contacted in a solution, and then dried and calcined to obtain the catalyst.
[0047] According to the present invention, the specific types of the molybdenum precursor and the bismuth precursor are not limited, as long as they provide the corresponding molybdenum and bismuth elements and can be dissolved in a solvent to form a uniform solvent, such as corresponding inorganic salts, nitrates, chloride salts, etc.
[0048] According to the present invention, the molybdenum precursor, the bismuth precursor, the molybdenum trioxide powder and the carrier source are mixed and contacted in the solution, which means that the molybdenum precursor, the bismuth precursor and the molybdenum trioxide powder are contacted in the presence of a solvent. When the mixed contact is carried out, the molybdenum precursor, the bismuth precursor, the molybdenum trioxide powder and the carrier source can be added to the solvent in sequence or simultaneously for mixing; the molybdenum precursor, the molybdenum trioxide powder and the carrier source can also be mixed with the solvent to obtain a mixed solution of the molybdenum-containing precursor, the molybdenum trioxide powder and the carrier source, the bismuth precursor can be mixed with the solvent to obtain a mixed solution of the bismuth-containing precursor, and then the mixed solution of the molybdenum-containing precursor, the molybdenum trioxide powder and the carrier source is mixed and contacted with the mixed solution of the bismuth-containing precursor; other methods can also be selected for mixed contact, wherein the carrier source can also be dispersed in the solvent as needed, and then mixed and contacted with other components. The present invention is not limited to the mixed contact methods listed above. When mixed contact or mixing to prepare the corresponding mixed solution, in order to make the mixing more uniform, the mixing can be carried out under heating and / or stirring conditions. For example, the mixture is mixed at a temperature of 30-100° C. and a stirring speed of 200-450 rpm for 5-30 min.
[0049] According to the present invention, the solvent used in step (1) is not particularly limited, as long as it can dissolve the molybdenum precursor and the bismuth precursor, it can be any solvent, including but not limited to water. The amount of the solvent is not particularly limited, as long as the molybdenum precursor and the bismuth precursor can be completely dissolved.
[0050] According to the present invention, as long as the purpose of the present invention can be achieved, the amount of molybdenum trioxide powder and molybdenum precursor is not particularly limited. In some embodiments, the mass ratio of molybdenum trioxide powder to molybdenum precursor is 1: (1-30), such as 1: 1, 1: 2, 1: 5, 1: 7, 1: 10, 1: 12, 1: 15, 1: 18, 1: 22, 1: 25 or 1: 30, preferably 1: (3-15). The above-mentioned embodiment is used to help reduce the volatilization loss of molybdenum components during long-term operation, thereby achieving long-term stable operation of the catalyst under high load.
[0051] According to the present invention, as long as the purpose of the present invention can be achieved, the specific type of the molybdenum trioxide powder is not particularly limited. In some embodiments, the molybdenum trioxide powder is an α-MoO3 crystal with a particle size of 300-600 mesh. The above-mentioned embodiment can improve the molybdenum content and the stability of the molybdenum component in the catalyst, which helps to reduce the volatilization loss of the molybdenum component during long-term operation, thereby achieving long-term stable operation of the catalyst under high load.
[0052] According to the present invention, as long as the purpose of the present invention can be achieved, the specific type of the carrier source is not particularly limited. In some embodiments, the carrier source is selected from at least one of silica sol, alumina sol, silica-alumina molecular sieve (such as ZSM-5 silica-alumina molecular sieve) and silica powder.
[0053] In the present invention, silica sol with a silica sol particle size of 10-25 nanometers (mass concentration of 30%) and ZSM-5 silica-alumina molecular sieve with a silica-alumina ratio of 150-200 and a mesh size of 800-1000 are used as examples to illustrate the advantages of the present invention, but the present invention is not limited to this.
[0054] According to the present invention, as long as the purpose of the present invention can be achieved, the acidic conditions in step (1) are not particularly limited. In some embodiments, the acidic conditions in step (1) are pH = 2-3. Using the above embodiment, the prepared catalyst has good activity and stability.
[0055] According to the present invention, in order to make the acidic condition pH=2-3, a pH adjuster may be used for adjustment, and the pH adjuster includes but is not limited to nitric acid.
[0056] According to the present invention, as long as the purpose of the present invention can be achieved, the amount of the surfactant is not particularly limited. In some embodiments, the mass ratio of the amount of the surfactant to the carrier is (0.005-0.05): 1. The above-mentioned embodiment helps the catalyst to form a smaller mesoporous structure, which can reduce the volatilization loss of the molybdenum component during long-term operation, thereby achieving long-term stable operation of the catalyst under high load.
[0057] According to the present invention, as long as the purpose of the present invention can be achieved, the specific type of the surfactant is not particularly limited. In some embodiments, the surfactant is selected from at least one of water-soluble urea compounds, polyols and quaternary ammonium salt surfactants, preferably including at least one of urea, ethylene glycol, hexadecyltrimethylammonium bromide (CTAB) and hexadecyltrimethylammonium chloride (CTAC). The above embodiment is used to better increase the activity and stability of the catalyst.
[0058] According to the present invention, in step (2), the precursor of the core structure, the precursor of B, the precursor of C, the precursor of D and the surfactant are mixed and contacted in the solution. It means that in the presence of a solvent, the precursor of the core structure, the precursor of B, the precursor of C, the precursor of D and the surfactant can be added to the solvent in sequence or simultaneously for mixed contact; the precursor of B, the precursor of C, the precursor of D can also be dissolved in the solvent to obtain a solution containing the precursor of B, the precursor of C, and the precursor of D, and the surfactant is dispersed in the solvent to obtain a surfactant solution of a certain concentration, and then the solution containing the precursor of B, the precursor of C, and the precursor of D and the surfactant solution of a certain concentration are sequentially or simultaneously added to the precursor of the core structure for mixing. When mixing and contacting or mixing to prepare the corresponding mixed solution, in order to make the mixing more uniform, the mixing can be carried out under heating and / or stirring conditions, for example, heating and stirring for 10-30 minutes at a temperature of 90-120°C and a stirring speed of 150-250 rpm. In addition, in order to improve the drying efficiency, the mixing can be stirred at a temperature greater than 100°C to form a slurry.
[0059] According to the present invention, the solvent used in step (2) is not particularly limited, as long as the solvent can dissolve the precursor of B, the precursor of C, and the precursor of D, including but not limited to water. The amount of the solvent used is not particularly limited, as long as the precursor of B, the precursor of C, and the precursor of D can be completely dissolved.
[0060] According to the present invention, as long as the purpose of the present invention can be achieved, the conditions for drying and calcining in step (2) are not particularly limited. In some embodiments, the drying method is spray drying, the heat source is air, the drying temperature is 280-400°C, the drying time is 0.5-1.0h, and the average diameter of the spray droplets is 30-120μm; in some embodiments, the calcining method is: carried out in an oxygen-containing atmosphere (such as air), the calcining temperature is 400-650°C, and the calcining time is 4-6h.
[0061] The third aspect of the present invention provides the use of the catalyst of the present invention in the preparation of nitrile compounds from C2-C5 hydrocarbon compounds.
[0062] The catalyst of the present invention not only has good catalyst activity in preparing nitrile compounds, but also can maintain a relatively high C2-C5 hydrocarbon compound conversion rate and a single-pass yield of nitrile compounds after long-term operation.
[0063] In the present invention, C2-C5 hydrocarbon compounds include C2-C5 alkanes and C2-C5 olefins.
[0064] A fourth aspect of the present invention provides a method for synthesizing acrylonitrile, the method comprising: subjecting propylene to an ammoxidation reaction under mixed gas conditions of an oxygen-containing atmosphere and ammonia.
[0065] The catalyst of the present invention can still maintain a relatively high propylene conversion rate and acrylonitrile per-pass yield after long-term operation.
[0066] According to some embodiments of the present invention, the conditions of the ammoxidation reaction include: the oxygen-containing atmosphere is oxygen, the molar ratio of propylene, oxygen-containing atmosphere (such as air) and ammonia is 1: (1.2-1.3): (9.6-10.0); and / or the reaction temperature is 420-435°C, and / or the reaction pressure (gauge pressure) is 0.06-0.14 MPa, and / or the reaction catalyst load is 0.08-0.12 h -1 .
[0067] The present invention will be described in detail below by way of examples. In the following examples and comparisons:
[0068] The specific surface area and pore size are measured using a Tristar physical adsorption instrument. Before the sample is tested, it needs to be heated and vacuumed for degassing. The porosity of the sample is measured at 77K, and the specific surface area is calculated using the Brunauer-Emmett-Teller (BET) method. The pore size distribution and pore volume can be calculated from the isothermal adsorption branch using the Barrettner-Joyner-Halenda (BJH) model.
[0069] The quantitative analysis of elements in the present invention is to obtain the element intensity distribution by line scanning test using scanning electron microscope-energy dispersive spectroscopy (SEM-EDS), and obtain the relative content of the elements by calculation;
[0070] The product gas was analyzed online by gas chromatography. The conversion rate of propylene, the selectivity of acrylonitrile and the single-pass yield were used as indicators for evaluating the catalyst performance. The definitions of the two are as follows:
[0071] Acrylonitrile conversion (%) = (moles of propylene reacted / moles of propylene fed) × 100%;
[0072] Acrylonitrile selectivity (%) = (moles of acrylonitrile produced / moles of propylene reacted) × 100%;
[0073] Acrylonitrile single-pass yield (%) = (number of moles of acrylonitrile produced / number of moles of propylene fed) × 100%.
[0074] Example 1
[0075] Preparation of ammonia oxidation catalyst:
[0076] (1) 211.9 g (NH4)6Mo7O 24 ·4H2O was heated at 100°C and dissolved in 200g of water, 23g of 600-mesh molybdenum trioxide powder and 900g of 30% silica sol were added, and the mixture was fully mixed to obtain a mixed solution I; 29.1g of Bi(NO3)3·5H2O was heated at 100°C and dissolved in 15g of water, and then added to the mixed solution I, and stirred at a stirring rate of 200 rpm for 20min, and then a nitric acid solution was added to adjust the pH to 2-3, and the stirring was continued to fully mix and hydrolyze to obtain a mixed solution II;
[0077] (2) After heating and stirring the mixed solution II at 60° C. for 15 min, 145.4 g of Ni(NO3)2·6H2O, 80.8 g of Fe(NO3)3·9H2O, 38.5 g of Mg(NO3)2·6H2O and 0.84 g of KNO3 were dissolved in 120 g of water and added to the mixed solution II. 50 mL of a 10% aqueous solution of hexadecyltrimethylammonium bromide was added under heating and stirring at 60° C., and the mixture was heated and stirred at 100° C. for 20 min to obtain a mixed slurry III. The stirring speed during stirring in step (2) was 250 rpm.
[0078] (3) The slurry III was spray dried at a drying temperature of 350° C. for a drying time of 0.5 hours to obtain particles, which were calcined at 600° C. in an air atmosphere for 3 hours to obtain an ammonia oxidation catalyst having a general composition formula of: 50 wt% Mo 10 Bi 0.4 4Fe 1.5 Ni 3.7 Mg 1.1 K 0.11 O 37.6 +50wt%SiO2;
[0079] The ammonia oxidation catalyst is divided into an inner core and an outer shell by scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS) analysis, and the radius of the catalyst particle is from the center of the catalyst particle to the surface of the particle, the radius of the inner core is 49% of the radius of the catalyst particle (wherein the inner core radius is 13.4 μm, and the catalyst particle radius is 27.3 μm), and the portion from the surface of the inner core to the surface of the catalyst particle is the outer shell. The radial change of the Mo content in the ammonia oxidation catalyst in this embodiment (from the center of the catalyst particle to the surface of the catalyst particle) is shown in the figure below: Figure 1 As shown; the content of element components and Figure 1 The vertical axis is proportional to the intensity, and the Mo content is proportional to Figure 1 Analytical calculations;
[0080] The content of each element in the catalyst was obtained by scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS) analysis as follows:
[0081] In the core and shell, Mo accounts for 68wt% and 32wt% of the total amount of Mo in the catalyst, respectively;
[0082] In the core and shell, Bi accounts for 57wt% and 43wt% of the total Bi in the catalyst, respectively;
[0083] In the core and shell, Fe accounts for 35wt% and 65wt% of the total amount of Fe in the catalyst, respectively;
[0084] In the core and shell, Ni accounts for 36wt% and 64wt% of the total Ni in the catalyst, respectively;
[0085] In the core and shell, Mg accounts for 33 wt% and 67 wt% of the total Mg in the catalyst, respectively;
[0086] In the core and shell, K accounts for 42 wt% and 58 wt% of the total amount of K in the catalyst, respectively;
[0087] In the core and shell, the carrier accounts for 61wt% and 39wt% of the total amount of the carrier in the catalyst, respectively;
[0088] The specific surface area of the catalyst is 47.3 m 2 / g, the pore sizes include 8nm (existing in the outer shell) and 22nm (existing in the inner core). The integral area of the pore size distribution is calculated to show that the two pore sizes account for 56% and 44% of the total pores of the catalyst, respectively.
[0089] Catalyst Evaluation:
[0090] In the presence of the ammoxidation catalyst prepared above, propylene ammoxidation was carried out to produce acrylonitrile. The reaction conditions were: in a φ38 mm fluidized bed reactor, reaction temperature: 420°C; reaction pressure: 0.085 MPa; catalyst loading: 300 g; catalyst propylene load (WWH): 0.12 h -1 ; Raw material ratio (molar): propylene: NH3: air (calculated as oxygen) = 1: 1.25: 9.7.
[0091] Catalyst evaluation results:
[0092] After 3 hours of operation, the propylene conversion rate was 98.87%, the acrylonitrile selectivity was 83.79%, and the acrylonitrile single-pass yield was 82.84%; after 500 hours of operation, the propylene conversion rate was 98.65%, the acrylonitrile selectivity was 83.43%, and the acrylonitrile single-pass yield was 82.30%.
[0093] Example 2
[0094] Preparation of ammonia oxidation catalyst:
[0095] (1) 211.9 g (NH4)6Mo7O 24 ·4H2O was heated at 100°C and dissolved in 200g of water, 23g of 600-mesh molybdenum trioxide powder and a carrier source dispersion containing 270g of ZSM-5 silica-alumina molecular sieve (obtained by mixing 270g of ZSM-5 silica-alumina molecular sieve with a molar silicon-alumina ratio of 150 and a mesh size of 800-1000 mesh with 630g of water) were added, and mixed thoroughly to obtain a mixed solution I; 29.1g of Bi(NO3)3·5H2O was heated at 100°C and dissolved in 15g of water, and then added to the mixed solution I, and stirred at a stirring speed of 200 rpm for 20min, and then a nitric acid solution was added to adjust the pH to 2-3, and stirring was continued to fully mix and hydrolyze to obtain a mixed solution II;
[0096] (2) After heating and stirring the mixed solution II at 60° C. for 15 min, 145.4 g of Ni(NO3)2·6H2O, 80.8 g of Fe(NO3)3·9H2O, 38.5 g of Mg(NO3)2·6H2O and 0.84 g of KNO3 were dissolved in 120 g of water and added to the mixed solution II. 50 mL of a 10% aqueous solution of hexadecyltrimethylammonium bromide was added under heating and stirring at 60° C., and the mixture was heated and stirred at 100° C. for 20 min to obtain a mixed slurry III. The stirring speed during stirring in step (2) was 250 rpm.
[0097] (3) The slurry III was spray dried at a drying temperature of 350° C. for a drying time of 0.5 hours to obtain particles, which were calcined at 550° C. in an air atmosphere for 3 hours to obtain an ammonia oxidation catalyst having a general composition formula of: 50 wt% Mo10 Bi 0.4 4Fe 1.5 Ni 3.7 Mg 1.1 K 0.11 O 37.6 +50wt% ZSM-5 silicon-alumina molecular sieve;
[0098] The ammonia oxidation catalyst is divided into an inner core and an outer shell by scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS) analysis, and the radius of the catalyst particle is from the center of the catalyst particle to the particle surface, the radius of the inner core is 52% of the radius of the catalyst particle (wherein the inner core radius is 14.6 μm, and the catalyst particle radius is 28.1 μm), and the portion along the surface of the inner core to the particle surface of the catalyst is the outer shell; the content of each element in the catalyst is as follows:
[0099] In the core and shell, Mo accounts for 66wt% and 34wt% of the total amount of Mo in the catalyst, respectively;
[0100] In the core and shell, Bi accounts for 56wt% and 44wt% of the total Bi in the catalyst, respectively;
[0101] In the core and shell, Fe accounts for 36 wt% and 64 wt% of the total amount of Fe in the catalyst, respectively;
[0102] In the core and shell, Ni accounts for 37 wt% and 63 wt% of the total Ni in the catalyst, respectively;
[0103] In the core and shell, Mg accounts for 33 wt% and 67 wt% of the total Mg in the catalyst, respectively;
[0104] In the core and shell, K accounts for 43 wt% and 57 wt% of the total amount of K in the catalyst, respectively;
[0105] In the core and shell, the carrier accounts for 60wt% and 40wt% of the total amount of the carrier in the catalyst, respectively;
[0106] The specific surface area of the catalyst is 51.0 m 2 / g, the pore sizes include 7nm (existing in the outer shell) and 23nm (existing in the inner core). The integral area of the pore size distribution is calculated to show that the two pore sizes account for 55% and 45% of the total pores of the catalyst, respectively.
[0107] The catalyst evaluation method is the same as in Example 1.
[0108] Catalyst evaluation results:
[0109] After 3 hours of operation, the propylene conversion rate was 98.78%, the acrylonitrile selectivity was 83.80%, and the acrylonitrile single-pass yield was 82.78%; after 500 hours of operation, the propylene conversion rate was 98.55%, the acrylonitrile selectivity was 83.32%, and the acrylonitrile single-pass yield was 82.11%.
[0110] Example 3
[0111] Preparation of ammonia oxidation catalyst:
[0112] (1) 211.9 g (NH4)6Mo7O 24 ·4H2O was heated at 100°C and dissolved in 200g of water, 23g of 600-mesh molybdenum trioxide powder and 900g of 30% silica sol were added, and the mixture was fully mixed to obtain a mixed solution I; 29.1g of Bi(NO3)3·5H2O was heated at 100°C and dissolved in 15g of water, and then added to the mixed solution I, and stirred at a stirring rate of 200 rpm for 20min, and then a nitric acid solution was added to adjust the pH to 2-3, and the stirring was continued to fully mix and hydrolyze to obtain a mixed solution II;
[0113] (2) After heating and stirring the mixed solution II at 60° C. for 15 min, 96.9 g of Ni(NO3)2·6H2O, 80.8 g of Fe(NO3)3·9H2O, 38.5 g of Mg(NO3)2·6H2O and 0.84 g of KNO3 were dissolved in 120 g of water and added to the mixed solution II. 50 mL of 10% urea aqueous solution was added under heating and stirring at 60° C., and the mixture was heated and stirred at 110° C. for 20 min to obtain a mixed slurry III. The stirring speed during stirring in step (2) was 250 rpm.
[0114] (3) The slurry III was spray dried at a drying temperature of 380° C. for a drying time of 0.5 hours to obtain particles, which were calcined at 600° C. in an air atmosphere for 3 hours to obtain an ammonia oxidation catalyst having a general composition formula of: 50 wt% Mo 10 Bi 0.4 4Fe 1.5 Ni 2.5 Mg 1.1 K 0.11 O 36.3 +50wt%SiO2;
[0115] The ammonia oxidation catalyst is divided into a core and a shell by scanning electron microscope-energy dispersive spectroscopy (SEM-EDS) analysis, and the radius of the catalyst particle is from the center of the catalyst particle to the particle surface, the radius of the core is 50% of the radius of the catalyst particle (wherein the core radius is 14.2 μm, and the catalyst particle radius is 28.4 μm), and the part along the surface of the core to the particle surface of the catalyst is the shell. The content of each element in the catalyst is as follows:
[0116] In the core and shell, Mo accounts for 67wt% and 33wt% of the total amount of Mo in the catalyst, respectively;
[0117] In the core and shell, Bi accounts for 56wt% and 44wt% of the total Bi in the catalyst, respectively;
[0118] In the core and shell, Fe accounts for 37 wt% and 63 wt% of the total amount of Fe in the catalyst, respectively;
[0119] In the core and shell, Ni accounts for 36wt% and 64wt% of the total Ni in the catalyst, respectively;
[0120] In the core and shell, Mg accounts for 32 wt% and 68 wt% of the total Mg in the catalyst, respectively;
[0121] In the core and shell, K accounts for 45wt% and 55wt% of the total amount of K in the catalyst, respectively;
[0122] In the core and shell, the carrier accounts for 58 wt% and 42 wt% of the total amount of the carrier in the catalyst, respectively;
[0123] The specific surface area of the catalyst is 48.5 m 2 / g, the pore sizes include 8nm (existing in the outer shell) and 23nm (existing in the inner core). The integral area of the pore size distribution is calculated to account for 57% and 43% of the total pores of the catalyst, respectively.
[0124] The catalyst evaluation method is the same as in Example 1.
[0125] Catalyst evaluation results:
[0126] After 3 hours of operation, the propylene conversion rate was 98.80%, the acrylonitrile selectivity was 83.72%, and the acrylonitrile single-pass yield was 82.71%; after 500 hours of operation, the propylene conversion rate was 98.53%, the acrylonitrile selectivity was 83.40%, and the acrylonitrile single-pass yield was 82.17%.
[0127] Example 4
[0128] Preparation of ammonia oxidation catalyst:
[0129] (1) 155.5 g (NH4)6Mo7O 24 ·4H2O was heated at 100°C and dissolved in 200g of water, 69g of 600-mesh molybdenum trioxide powder and 900g of 30% silica sol were added, and the mixture was fully mixed to obtain a mixed solution I; 29.1g of Bi(NO3)3·5H2O was heated at 100°C and dissolved in 15g of water, and then added to the mixed solution I, and stirred at a stirring speed of 200 rpm for 20min, and then a nitric acid solution was added to adjust the pH to 2-3, and the stirring was continued to fully mix and hydrolyze to obtain a mixed solution II;
[0130] (2) After heating and stirring the mixed solution II at 60° C. for 15 min, 145.4 g of Ni(NO3)2·6H2O, 80.8 g of Fe(NO3)3·9H2O, 38.5 g of Mg(NO3)2·6H2O and 0.84 g of KNO3 were dissolved in 120 g of water and added to the mixed solution II. 50 mL of a 10% aqueous solution of hexadecyltrimethylammonium bromide was added under heating and stirring at 60° C., and the mixture was heated and stirred at 100° C. for 20 min to obtain a mixed slurry III. The stirring speed during stirring in step (2) was 250 rpm.
[0131] (3) The slurry III was spray-dried at a drying temperature of 350° C. for a drying time of 0.5 hour to obtain a granular material. The granular material was calcined at 600° C. for 3 hours in an air atmosphere to obtain an ammonia oxidation catalyst.
[0132] The ammonia oxidation catalyst is divided into a core and a shell by scanning electron microscope-energy dispersive spectroscopy (SEM-EDS) analysis, and the radius of the catalyst particle is from the center of the catalyst particle to the particle surface, the radius of the core is 56% of the radius of the catalyst particle (wherein the core radius is 16.0 μm, and the catalyst particle radius is 28.6 μm), and the part along the surface of the core to the particle surface of the catalyst is the shell. The content of each element in the catalyst is as follows:
[0133] In the core and shell, Mo accounts for 82 wt% and 18 wt% of the total amount of Mo in the catalyst, respectively;
[0134] In the core and shell, Bi accounts for 60wt% and 40wt% of the total Bi in the catalyst, respectively;
[0135] In the core and shell, Fe accounts for 35wt% and 65wt% of the total amount of Fe in the catalyst, respectively;
[0136] In the core and shell, Ni accounts for 37 wt% and 63 wt% of the total Ni in the catalyst, respectively;
[0137] In the core and shell, Mg accounts for 33 wt% and 67 wt% of the total Mg in the catalyst, respectively;
[0138] In the core and shell, K accounts for 41 wt% and 59 wt% of the total amount of K in the catalyst, respectively;
[0139] In the core and shell, the carrier accounts for 62 wt% and 38 wt% of the total amount of the carrier in the catalyst, respectively;
[0140] The specific surface area of the catalyst is 43.1 m 2 / g, the pore sizes include 9nm (existing in the outer shell) and 24nm (existing in the inner core). The integral area of the pore size distribution is calculated, and the proportion of the two pore sizes in the total pores of the catalyst is 53% and 47%, respectively.
[0141] The catalyst evaluation method is the same as in Example 1.
[0142] Catalyst evaluation results:
[0143] After 3 hours of operation, the propylene conversion rate was 97.56%, the acrylonitrile selectivity was 82.20%, and the acrylonitrile single-pass yield was 80.19%; after 500 hours of operation, the propylene conversion rate was 96.82%, the acrylonitrile selectivity was 81.61%, and the acrylonitrile single-pass yield was 79.01%.
[0144] Example 5
[0145] Preparation of ammonia oxidation catalyst:
[0146] (1) 230.8 g (NH4)6Mo7O 24 ·4H2O was heated at 100°C and dissolved in 200g of water, 7.7g of 600-mesh molybdenum trioxide powder and 900g of 30% silica sol were added, and the mixture was fully mixed to obtain a mixed solution I; 29.1g of Bi(NO3)3·5H2O was heated at 100°C and dissolved in 15g of water, and then added to the mixed solution I, and stirred at a stirring speed of 200 rpm for 20min, and then a nitric acid solution was added to adjust the pH to 2-3, and the stirring was continued to fully mix and hydrolyze to obtain a mixed solution II;
[0147] (2) After heating and stirring the mixed solution II at 60° C. for 15 min, 145.4 g of Ni(NO3)2·6H2O, 80.8 g of Fe(NO3)3·9H2O, 38.5 g of Mg(NO3)2·6H2O and 0.84 g of KNO3 were dissolved in 120 g of water and added to the mixed solution II. 50 mL of a 10% aqueous solution of hexadecyltrimethylammonium bromide was added under heating and stirring at 60° C., and the mixture was heated and stirred at 100° C. for 20 min to obtain a mixed slurry III. The stirring speed during stirring in step (2) was 250 rpm.
[0148] (3) The slurry III was spray-dried at a drying temperature of 350° C. for a drying time of 0.5 hour to obtain a granular material. The granular material was calcined at 600° C. for 3 hours in an air atmosphere to obtain an ammonia oxidation catalyst.
[0149] The ammonia oxidation catalyst is divided into a core and a shell by scanning electron microscope-energy dispersive spectroscopy (SEM-EDS) analysis, and the radius of the catalyst particle is from the center of the catalyst particle to the particle surface, the radius of the core is 45% of the radius of the catalyst particle (wherein the core radius is 13.1 μm, and the catalyst particle radius is 29.1 μm), and the part along the surface of the core to the particle surface of the catalyst is the shell. The content of each element in the catalyst is as follows:
[0150] In the core and shell, Mo accounts for 56wt% and 44wt% of the total amount of Mo in the catalyst, respectively;
[0151] In the core and shell, Bi accounts for 58wt% and 42wt% of the total Bi in the catalyst, respectively;
[0152] In the core and shell, Fe accounts for 35wt% and 65wt% of the total amount of Fe in the catalyst, respectively;
[0153] In the core and shell, Ni accounts for 37 wt% and 63 wt% of the total Ni in the catalyst, respectively;
[0154] In the core and shell, Mg accounts for 33 wt% and 67 wt% of the total Mg in the catalyst, respectively;
[0155] In the core and shell, K accounts for 42 wt% and 58 wt% of the total amount of K in the catalyst, respectively;
[0156] In the core and shell, the carrier accounts for 61wt% and 39wt% of the total amount of the carrier in the catalyst, respectively;
[0157] The specific surface area of the catalyst is 50.9 m 2 / g, the pore sizes include 7nm (existing in the outer shell) and 23nm (existing in the inner core). The integral area of the pore size distribution is calculated and the proportions of the two pore sizes are 52% and 48% respectively.
[0158] The catalyst evaluation method is the same as in Example 1;
[0159] Catalyst evaluation results:
[0160] After 3 hours of operation, the propylene conversion rate was 97.72%, the acrylonitrile selectivity was 82.05%, and the acrylonitrile single-pass yield was 80.18%; after 500 hours of operation, the propylene conversion rate was 96.85%, the acrylonitrile selectivity was 81.36%, and the acrylonitrile single-pass yield was 78.79%.
[0161] Example 6
[0162] Preparation of ammonia oxidation catalyst:
[0163] (1) 211.9 g (NH4)6Mo7O 24 ·4H2O was heated at 100°C and dissolved in 200g of water, 23g of 600-mesh molybdenum trioxide powder and 900g of 30% silica sol were added, and the mixture was fully mixed to obtain a mixed solution I; 29.1g of Bi(NO3)3·5H2O was heated at 100°C and dissolved in 15g of water, and then added to the mixed solution I, and stirred at a stirring speed of 200 rpm for 20min, and then nitric acid solution was added to adjust the pH to 2-3, and stirring was continued to fully mix and hydrolyze to obtain a solution II;
[0164] (2) After heating and stirring the mixed solution II at 60° C. for 15 min, 145.4 g of Ni(NO3)2·6H2O, 80.8 g of Fe(NO3)3·9H2O, 38.5 g of Mg(NO3)2·6H2O and 0.84 g of KNO3 were dissolved in 120 g of water and added to the mixed solution II. 50 mL of a 10% aqueous solution of hexadecyltrimethylammonium bromide was added under heating and stirring at 60° C., and the mixture was heated and stirred at 100° C. for 20 min to obtain a mixed slurry III. The stirring speed during stirring in step (2) was 250 rpm.
[0165] (3) The slurry III was spray-dried at a drying temperature of 350° C. for a drying time of 0.5 hour to obtain a granular material. The granular material was calcined at 650° C. for 3 hours in an air atmosphere to obtain an ammonia oxidation catalyst.
[0166] The ammonia oxidation catalyst is divided into a core and a shell by scanning electron microscope-energy dispersive spectroscopy (SEM-EDS) analysis, and the radius of the catalyst particle is from the center of the catalyst particle to the particle surface, the radius of the core is 52% of the radius of the catalyst particle (wherein the core radius is 12.8 μm, and the catalyst particle radius is 24.6 μm), and the part along the surface of the core to the particle surface of the catalyst is the shell. The content of each element in the catalyst is as follows:
[0167] In the core and shell, Mo accounts for 67wt% and 33wt% of the total amount of Mo in the catalyst, respectively;
[0168] In the core and shell, Bi accounts for 57wt% and 43wt% of the total Bi in the catalyst, respectively;
[0169] In the core and shell, Fe accounts for 35wt% and 65wt% of the total amount of Fe in the catalyst, respectively;
[0170] In the core and shell, Ni accounts for 36wt% and 64wt% of the total Ni in the catalyst, respectively;
[0171] In the core and shell, Mg accounts for 35wt% and 65wt% of the total Mg in the catalyst, respectively;
[0172] In the core and shell, K accounts for 43 wt% and 57 wt% of the total amount of K in the catalyst, respectively;
[0173] In the core and shell, the carrier accounts for 61wt% and 39wt% of the total amount of the carrier in the catalyst, respectively;
[0174] The specific surface area of the catalyst is 32.0 m 2 / g, the pore sizes include 15nm (existing in the outer shell) and 32nm (existing in the inner core). The integral area of the pore size distribution is calculated to show that the two pore sizes account for 67% and 33% of the total pores of the catalyst, respectively.
[0175] The catalyst evaluation method is the same as in Example 1.
[0176] Catalyst evaluation results:
[0177] After 3 hours of operation, the propylene conversion rate was 97.48%, the acrylonitrile selectivity was 82.32%, and the acrylonitrile single-pass yield was 80.24%; after 500 hours of operation, the propylene conversion rate was 96.75%, the acrylonitrile selectivity was 81.74%, and the acrylonitrile single-pass yield was 79.08%.
[0178] Example 7
[0179] Preparation of ammonia oxidation catalyst:
[0180] (1) 211.9 g (NH4)6Mo7O 24 ·4H2O was heated at 100°C and dissolved in 200g of water, 23g of 600-mesh molybdenum trioxide powder and 900g of 30% silica sol were added, and the mixture was fully mixed to obtain a mixed solution I; 29.1g of Bi(NO3)3·5H2O was heated at 100°C and dissolved in 15g of water, and then added to the mixed solution I, and stirred at a stirring rate of 200 rpm for 20min, and then a nitric acid solution was added to adjust the pH to 2-3, and the stirring was continued to fully mix and hydrolyze to obtain a mixed solution II;
[0181] (2) After heating and stirring the mixed solution II at 60° C. for 15 min, 145.4 g of Ni(NO3)2·6H2O, 80.8 g of Fe(NO3)3·9H2O, 38.5 g of Mg(NO3)2·6H2O and 0.84 g of KNO3 were dissolved in 120 g of water and added to the mixed solution II. 5 mL of a 10% aqueous solution of hexadecyltrimethylammonium bromide was added under heating and stirring, and the mixture was heated and stirred at 100° C. for 20 min to obtain a mixed slurry III. The stirring speed during stirring in step (2) was 250 rpm.
[0182] (3) The slurry III was spray-dried at a drying temperature of 350° C. for a drying time of 0.5 hour to obtain a granular material. The granular material was calcined at 600° C. for 3 hours in an air atmosphere to obtain an ammonia oxidation catalyst.
[0183] The ammonia oxidation catalyst is divided into a core and a shell by scanning electron microscope-energy dispersive spectroscopy (SEM-EDS) analysis, and the radius of the catalyst particle is from the center of the catalyst particle to the particle surface, the radius of the core is 50% of the radius of the catalyst particle (wherein the core radius is 13.7 μm, and the catalyst particle radius is 27.4 μm), and the part along the surface of the core to the particle surface of the catalyst is the shell. The content of each element in the catalyst is as follows:
[0184] In the core and shell, Mo accounts for 64wt% and 36wt% of the total amount of Mo in the catalyst, respectively;
[0185] In the core and shell, Bi accounts for 56wt% and 44wt% of the total Bi in the catalyst, respectively;
[0186] In the core and shell, Fe accounts for 37 wt% and 63 wt% of the total amount of Fe in the catalyst, respectively;
[0187] In the core and shell, Ni accounts for 36wt% and 64wt% of the total Ni in the catalyst, respectively;
[0188] In the core and shell, Mg accounts for 33 wt% and 67 wt% of the total Mg in the catalyst, respectively;
[0189] In the core and shell, K accounts for 42 wt% and 58 wt% of the total amount of K in the catalyst, respectively;
[0190] In the core and shell, the carrier accounts for 60wt% and 40wt% of the total amount of the carrier in the catalyst, respectively;
[0191] The specific surface area of the catalyst is 32.7 m 2 / g, the pore sizes include 10nm (existing in the outer shell) and 31nm (existing in the inner core). The integral area of the pore size distribution is calculated to show that the two pore sizes account for 26% and 74% of the total pores of the catalyst, respectively.
[0192] The catalyst evaluation method is the same as in Example 1.
[0193] Catalyst evaluation results:
[0194] After 3 hours of operation, the propylene conversion rate was 97.52%, the acrylonitrile selectivity was 82.20%, and the acrylonitrile single-pass yield was 80.16%; after 500 hours of operation, the propylene conversion rate was 96.73%, the acrylonitrile selectivity was 81.54%, and the acrylonitrile single-pass yield was 78.87%.
[0195] Comparative Example 1
[0196] Preparation of ammonia oxidation catalyst:
[0197] (1) 240.1 g (NH4)6Mo7O 24 ·4H2O was dissolved in 200g water by heating at 100°C, 900g of 30% silica sol was added, and the mixture was fully mixed to obtain a mixed solution I; 29.1g of Bi(NO3)3·5H2O was dissolved in 15g water by heating at 100°C, and the mixture was added to the mixed solution I, and the mixture was stirred at a stirring rate of 200 rpm for 20min to obtain a mixed solution II;
[0198] (2) 145.4 g of Ni(NO3)2·6H2O, 80.8 g of Fe(NO3)3·9H2O, 38.5 g of Mg(NO3)2·6H2O and 0.84 g of KNO3 were dissolved in 120 g of water and added into the mixed solution II. 50 mL of a 10% aqueous solution of hexadecyltrimethylammonium bromide was added under heating and stirring. The mixture was heated and stirred at 100°C for 20 min to obtain a mixed slurry III. The stirring speed in step (2) was 250 rpm.
[0199] (3) The slurry III was spray dried at a drying temperature of 350° C. for a drying time of 0.5 hours to obtain particles, which were calcined at 600° C. in an air atmosphere for 3 hours to obtain an ammonia oxidation catalyst having a general composition formula of: 50 wt% Mo 10 Bi 0.4 4Fe 1.5 Ni 3.7 Mg 1.1 K 0.11 O 37.6 +50wt%SiO2;
[0200] Scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS) analysis showed that the elemental components of the catalyst were evenly distributed and there was no obvious core-shell structure.
[0201] The specific surface area of the catalyst is 46.8 m 2 / g, the pore sizes include 9nm and 26nm. The integral area of pore size distribution is calculated to show that the proportions of the two pore sizes in the total pores of the catalyst are 59% and 41% respectively.
[0202] The catalyst evaluation method is the same as in Example 1.
[0203] Catalyst evaluation results:
[0204] After 3 hours of operation, the propylene conversion rate was 95.67%, the acrylonitrile selectivity was 79.61%, and the acrylonitrile single-pass yield was 76.16%; after 500 hours of operation, the propylene conversion rate was 93.58%, the acrylonitrile selectivity was 78.55%, and the acrylonitrile single-pass yield was 73.51%.
[0205] It can be seen from the results of the above examples that the examples 1-7 using the catalyst of the present invention have the ability to maintain a relatively high propylene conversion rate and acrylonitrile per-pass yield in the synthesis method for acrylonitrile after long-term operation.
[0206] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A core-shell ammonia oxidation catalyst, characterized in that: The catalyst comprises a carrier and an active component; The general formula of the active component is Mo 10 Bi a B b C c D d O x ; B is selected from at least one of the Group VIII metal elements; C is selected from at least one of the alkaline earth metal elements; D is selected from at least one of the alkali metal elements; a, b, c and d represent the molar content of Bi, B, C and D relative to Mo respectively; a is in the range of 0.05-8.0, b is in the range of 0.02-10.0, c is in the range of 0.02-6.0, d is in the range of 0.05-5.0, and x is determined by the atomic ratio and valence state of the elements other than oxygen in the general formula of the active component; Among them, Mo exists in the form of bismuth molybdate, molybdenum trioxide, and molybdate simultaneously; The mesoscopic structure of the catalyst comprises an inner core and an outer shell; the main components of the inner core of the catalyst comprise bismuth molybdate, molybdenum trioxide and a carrier; the main components of the outer shell of the catalyst comprise molybdate and a carrier.
2. The catalyst according to claim 1, wherein a is in the range of 0.05-4; and / or b is in the range of 0.1-10; and / or c is in the range of 0.1-6; and / or d is in the range of 0.05-2; and / or The molybdenum content of the core and the shell is different based on the total weight of molybdenum in the catalyst; Preferably, based on the total weight of molybdenum in the catalyst, the content of molybdenum in the inner core is higher than the content of molybdenum in the outer shell; More preferably, based on the total amount of molybdenum in the catalyst, the mass content of molybdenum in the inner core is 60-80wt%, and the mass content of molybdenum in the outer shell is 20-40wt%.
3. The catalyst according to claim 1 or 2, wherein Based on the total amount of carriers in the catalyst, the carriers in the inner core account for 50-65wt% of the total amount of carriers in the catalyst, and the carriers in the outer shell account for 35-50wt% of the total amount of carriers in the catalyst; and / or Based on the total amount of bismuth in the catalyst, the bismuth in the inner core accounts for 55-65wt% of the total amount of bismuth in the catalyst, and the bismuth in the outer shell accounts for 35-45wt% of the total amount of bismuth in the catalyst; and / or Based on the total amount of B element in the catalyst, the B element in the core accounts for 30-45wt% of the total amount of B element in the catalyst, and the B element in the shell accounts for 55-70wt% of the total amount of B element in the catalyst; and / or Based on the total amount of C elements in the catalyst, the C elements in the core account for 30-45wt% of the total amount of C elements in the catalyst, and the C elements in the shell account for 55-70wt% of the total amount of C elements in the catalyst; and / or Based on the total amount of D element in the catalyst, the D element in the core accounts for 35-45wt% of the total amount of D element in the catalyst, and the D element in the shell accounts for 55-65wt% of the total amount of D element in the catalyst.
4. The catalyst according to any one of claims 1 to 3, wherein B is at least one selected from iron, cobalt, nickel, ruthenium, rhodium, palladium, osmium, iridium and platinum, preferably at least one selected from iron, cobalt and nickel; and / or C is at least one selected from magnesium, calcium, strontium and barium, preferably magnesium and / or calcium; and / or D is at least one selected from sodium, potassium, rubidium and cesium, preferably potassium.
5. The catalyst according to any one of claims 1 to 4, wherein The specific surface area of the catalyst is 35-60m 2 / g; and / or The pores with a pore size of 20-35 nm on the inner core account for 40-50% of the total pores of the catalyst; and / or The pores with a pore size of 6-12 nm on the shell account for 50-60% of the total pores of the catalyst; and / or The radius of the catalyst particle is from the center of the catalyst particle to the particle surface, the radius of the inner core is 40-60% of the radius of the catalyst particle, and the part along the surface of the inner core to the catalyst particle surface is the outer shell.
6. The catalyst according to any one of claims 1 to 5, wherein The mass ratio of the active ingredient to the carrier is (1.5-0.8):1, preferably (1.2-1.0):1; and / or The support includes alumina and / or silica.
7. A method for preparing the catalyst according to any one of claims 1 to 6, characterized in that: The method includes: (1) a molybdenum precursor, a bismuth precursor, a molybdenum trioxide powder, and a carrier source are mixed and contacted in a solution, and then hydrolyzed and compounded under acidic conditions to obtain a precursor of a core structure; (2) The precursor of the core structure, the precursor of B, the precursor of C, the precursor of D and the surfactant are mixed and contacted in a solution, and then dried and calcined to obtain the catalyst.
8. The preparation method according to claim 7, wherein: The mass ratio of molybdenum trioxide powder to molybdenum precursor is 1:(1-30), preferably 1:(3-15), based on the molar amount of molybdenum provided; and / or The molybdenum trioxide powder is of α-MoO3 crystal type, and the particle size is 300-600 mesh; and / or The carrier source is selected from at least one of silica sol, alumina sol, silica-alumina molecular sieve, and silica powder; and / or The acidic condition in step (1) is pH=2-3; and / or The mass ratio of the amount of the surfactant to the carrier source is (0.005-0.05):1; and / or The surfactant is selected from at least one of water-soluble urea compounds, polyols and quaternary ammonium salt surfactants, and preferably includes at least one of urea, ethylene glycol, hexadecyltrimethylammonium bromide and hexadecyltrimethylammonium chloride.
9. Use of the catalyst according to any one of claims 1 to 6 in the preparation of nitrile compounds from C2-C5 hydrocarbon compounds.
10. A method for synthesizing acrylonitrile, characterized in that: The method comprises: carrying out an ammoxidation reaction of propylene under the condition of a mixed gas of an oxygen-containing atmosphere and ammonia; Preferably, the conditions of the ammoxidation reaction include: The oxygen-containing atmosphere is calculated as oxygen, and the molar ratio of propylene, oxygen-containing atmosphere and ammonia is 1:(1.2-1.3):(9.6-10.0); and / or The reaction temperature is 420-435°C, and / or The reaction pressure is 0.06-0.14MPa, and / or The reaction catalyst load is 0.08-0.12h -1 .
Citation Information
Patent Citations
Method for preparing catalyst for acrolein and acrylic acid
CN101690900A
Method for preparing doped nanometer bismuth vanadate yellow pigment
CN107629483A
Retention of activity of molybdernum-containing metallic oxide catalyst
CN1179359A
Solid catalyst for preparing nitrile compounds
KR1019990085328A
Solid catalyst with core-shell catalytic phase and a method of preparation thereof
US6924387B1
